Chronic constant light exposure aggravates high fat diet-induced renal injury in rats - Xing, Lin; Wu, Shanyu; Shi, Ying; Yue, Fangzhi; Wei, Lin; Russell, Ryan; Zhang, Dongmei (Frontiers in Endocrinology, 2022)
Obesity-related kidney disease is now recognized as a global health issue, with a substantial number of patients developing progressive renal failure and end-stage renal disease. Interestingly, recent studies indicate light pollution is a novel environmental risk factor for chronic kidney disease. However, the impact of light pollution on obesity-related kidney disease remains largely unknown, with its underlying mechanism insufficiently explained. Renal hypoxia induced factor 1α (HIF1α) is critical in the development of glomerulosclerosis and renal fibrosis. The present study explored effects of constant light exposure on high fat diet (HFD) -induced renal injury and its association with HIF1α signal pathway. Thirty-two male Sprague Dawley rats were divided into four groups according to diet (HFD or normal chow diet) and light cycles (light/dark or constant light). After 16 weeks treatment, rats were sacrificed and pathophysiological assessments were performed. In normal chow fed rats, constant light exposure led to glucose abnormalities and dyslipidemia. In HFD fed rats, constant light exposure exacerbated obesity, glucose abnormalities, insulin resistance, dyslipidemia, renal functional decline, proteinuria, glomerulomegaly, renal inflammation and fibrosis. And, constant light exposure caused an increase in HIF1α and a decrease in prolyl hydroxylase domain 1 (PHD1) and PHD2 expression in kidneys of HFD-fed rats. Then, we demonstrated that BMAL1 bound directly to the promoters of PHD1 in mouse podocyte clone 5 cell line (MPC5) by ChIP assays. In conclusion, chronic constant light exposure aggravates HFD-induced renal injuries in rats, and it is associated with activation of HIF1α signal pathway.